Design Exploration of Machine Learning Data-Flows onto Heterogeneous Reconﬁgurable Hardware - Oliveira, Westerley; Canesche, Michael; Reis, Lucas; Nacif, José; Ferreira, Ricardo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2020)
Machine/Deep learning applications are currently the center of the attention of both industry and academia, turning these applications acceleration a very relevant research topic. Acceleration comes in different ﬂavors, including parallelizing routines on a GPU, FPGA, or CGRA. In this work, we explore the placement and routing of Machine Learning applications dataﬂow graphs onto three heterogeneous CGRA architectures. We compare our results with the homogeneous case and with one of the state-of-the-art tools for placement and routing (P&R). Our algorithm executed, on average, 52% faster than Versatile Place&Routing (VPR) 8.1. Furthermore, a heterogeneous architecture reduces the cost without losing performance in 76% of the cases.